Exploring positive and negative intersectionality effects: an employment study of neurodiverse UK military veterans - Allen, Robby A.; Dickmann, Michael; Priscott, Tamsin; White, Gareth R. T. (Taylor & Francis, 2023)
Intersectional studies have examined the impact of personal characteristics upon employment experience, but little attention has been given to specificities of the neurodiverse and the military veteran. Both may possess skills and abilities that are desirable but there are several negative stereotypes that impact the acquisition and retention of work. Additionally, talent sourcing practices by employers can favour neurotypical people with a civilian background. Adopting a multi-method approach, this study explores barriers to employment and how they are compounded at the intersection of being a neurodiverse veteran (NDV). We surveyed 232 people with a medically diagnosed condition and conducted 21 semi-structured interviews to explore NDVs’ views about how the recruitment process and HR practices impact their employment relationship. Extant studies often depict the intersection of qualities to be disadvantageous for the populations studied, however, our research suggests that NDVs can have highly beneficial work capabilities. Our practical contribution includes the identification of key positive and negative aspects in the employment of NDVs and how organizations can refine their talent sourcing and management. Our theoretical contribution is made through a framework depicting the influences on NDVs’ employment relationships and a set of propositions that illuminate the intersectionality of neurodiverse and military veterans at work.
Keywords: Intersectionality; HRM; neurodiversity; military veteran; reasonable adjustments